LENGHT - WEIGHT RELATIONSHIP ANDDENSITY OF Littorina melanostomaANDNerita lineataIN MANGROVE ECOSYSTEMSOF BASILAM BARU VILLAGE DUMAI CITY, RIAU PROVINCE - Gafnie, Ghassani Razan; Amin, Bintal; Thamrin, Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractLittorina melanostoma andNerita lineata is a type of snail that use mangrove ecosystems as one of the habitats. Dumai is one of the industrial cities in the province of Riau, where various kinds of human activity can disrupt the ecosystem of mangroves and its associated biota.This research was conducted in January 2018 in mangrove ecosystem of Basilam Baru Dumai City aiming to find out the lenght weight relationship, snail densities, types of mangroves and between mangroverelationship with snails density. That sampling was done by using the transek method on two stations.The results showed the length weight relationship is a negative allometric with the higher density at station I. Six (6) species were found in the mangrove.Relationship between mangrove density with density ofL. melanostomawas found to be weak while the relationship of the density of mangrove with density N. lineata wasstrong relationship.Keywords: Littorina melanostoma,Nerita lineata, Length Weight Relationship, Mangrove